Peningkatan Pelaksanaan Fungsi Badan Pengawas Pemilu (Bawaslu) dalam Mengatasi Pelanggaran Pemilu Legislatif Tahun 2024 di Kota Kupang - Maria Ayentusianti Mamo; Saryono Yohanes; Hernimus Ratu Udju (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The process of holding elections must implement the principles of the election itself, namely: Honest, Fair, Direct, Public, Free, Secret, and Transparent. However, the implementation of general elections in Indonesia is inseparable from all forms of election violations and election disputes. One of the institutions responsible for supervising general elections in Indonesia is the General Election Supervisory Agency (BAWASLU). This type of research is empirical juridical legal research using the type of legal sociology study (Socio-legal research) which emphasizes the importance of interview steps and literature studies and qualitative descriptive analysis, namely by explaining, elucidating, and describing problems and close solutions. The results of this study show that: (1) The main functions of Bawaslu include monitoring, studying, and supervising the election process and preventing election violations. Therefore, monitoring, studying, preventing and supervising every stage of the general election in Kupang City properly and the implementation of Bawaslu's functions involves monitoring, investigating, and enforcing rules during the election process. (2) Efforts made by Bawaslu include maintaining the integrity of the election by ensuring that all processes run according to the rules, preventing and handling violations such as money politics and black campaigns. The efforts made by the Kupang City Bawaslu in overcoming Election Violations in Kupang City can be considered successful.